Two new species of Pterostylis (Orchidaceae; Orchidoideae) from the Sunset Country, Victoria, Australia - Reiter, Noushka; Kosky, William; Clements, Mark (Phytotaxa, 2021)
In northwestern Victoria, Australia, the Pterostylis (Orchidaceae) section Oligochaetochilus ‘rufa group’ comprises several little studied and poorly collected taxa. We surveyed populations of the rufa group in the Sunset Country, collecting information on the habitat and vegetation community. Fourteen sites were surveyed for plants with affinities to P. biseta and P. exelsa. We measured 23 morphological traits for each of 31 field-collected and seven herbarium specimens from this area. Multivariate analyses were undertaken, with cluster analysis and ordination performed on range-standardised data. Three distinct groups were present in both an ordination and dendrogram, with key diagnostic characters relating to the labellum. These groups were compared against other morphologically similar species of Pterostylis. Our analyses confirmed one of these groups as P. biseta, which is widespread in northwestern Victoria, and two as previously undescribed, putatively rare taxa, described here.